2022
DOI: 10.1136/bmjopen-2021-055432
|View full text |Cite
|
Sign up to set email alerts
|

Vocational and psychosocial predictors of medical negligence claims among Australian doctors: a prospective cohort analysis of the MABEL survey

Abstract: ObjectiveTo understand the association between medical negligence claims and doctors’ sex, age, specialty, working hours, work location, personality, social supports, family circumstances, self-rated health, self-rated life satisfaction and presence of recent injury or illness.Design and settingProspective cohort study of Australian doctors.Participants12 134 doctors who completed the Medicine in Australia: Balancing Employment and Life survey between 2013 and 2019.Primary outcome measureDoctors named as a def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…Conversely, legal training organized by hospitals, having publicity of the rule of law for hospital staff, participating in legal training organized by hospitals, being willing to participate in law training organized by hospitals, and having a well-established rule of law in the hospital were found to be protective factors. These findings are consistent with the current literature, which also elucidated that conducting standardized high-level hospitals [37], providing preservice skills training [38], having older physicians [10], male physicians [10,11,39], a higher professional level [11], and implementing specific and appropriate laws and regulations [40] were significantly associated with medical disputes. Higher-ranked physicians often face heavier workload, which can adversely affect their health and the quality of their services [11].…”
Section: Principal Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, legal training organized by hospitals, having publicity of the rule of law for hospital staff, participating in legal training organized by hospitals, being willing to participate in law training organized by hospitals, and having a well-established rule of law in the hospital were found to be protective factors. These findings are consistent with the current literature, which also elucidated that conducting standardized high-level hospitals [37], providing preservice skills training [38], having older physicians [10], male physicians [10,11,39], a higher professional level [11], and implementing specific and appropriate laws and regulations [40] were significantly associated with medical disputes. Higher-ranked physicians often face heavier workload, which can adversely affect their health and the quality of their services [11].…”
Section: Principal Findingssupporting
confidence: 91%
“…Previous studies have highlighted that institutional failures in the legal framework, inappropriate internal incentives, patient-physician mistrust, heavy physician workloads, and medical malpractice are risk factors [6][7][8] contributing to medical disputes. Conversely, being female, implementing positive psychology interventions, and adopting healthy lifestyle management responsibilities are protective factors for medical disputes [9][10][11][12]. Previously, we found that hospital legal constructions play an important role in regulating medical disputes from the perspective of hospital administrators [12].…”
Section: Introductionmentioning
confidence: 86%
“…We identified several unmodifiable risk factors that contribute to the occurrence of medical disputes among healthcare professionals. These findings are consistent with previous studies, 2,3,15,[21][22][23] which further strengthen their significance. Recognizing and addressing these unmodifiable risk factors can empower healthcare institutions and policymakers to develop targeted interventions and strategies that effectively address the specific challenges faced by healthcare professionals at higher risk of medical disputes.…”
Section: Implications For Healthcare Institutions and Policymakerssupporting
confidence: 93%
“…Poor mental health states, including stress, depression, burnout, and poor overall well-being, have been associated with medical error [ 31 , 32 ]. A recent study highlights that acute and recent injury may contribute to this risk, which mirrors these research findings and reinforces prior recommendations to intensify preventive efforts aimed at improving doctors’ health and well-being [ 33 ].…”
Section: Discussionsupporting
confidence: 78%